Identification and ranking of factors affecting behavioral economics in Iran - Ahmadi, Seyed Ali Akbar; Salamzadeh, Yashar; Ranjbar, Lia (Journal of Entrepreneurship, Business and Economics, 2016)
Purpose- Since economics is the science of choice and if we conside the human being as a selector, it should be noted how the function of selection is formed and how it can psychologically measure and analyze activities such as intentions, motives, opinions, attitudes and expectations. The aims of this study were to identify and rank the factors affecting behavioral economics and its use. Design/methodology/approach- In this deseriptive -analytic study, 385 in dividuals were selected using the Cochran formula. Data were gathered through a questionnaire and analyzed using arachnoid diagram rating and spss software package. Findings- Generally, fairness, risk and inequity aversion dimensions have more important roles in behavioral economics of Iran community, while, mimicry, sel fishness and economic intelligence have less significant roles. All hypotheses of the study were confirmed (p<0.05) and although the hypothesis related to selfishness was rejected, according to the participants, role of selfishness dimen-sion is high among Iran community. Research limitations/implications- It can be concluded that the behavior and habits of other people have no significant role in behavioral economy of Iran community, that might be due to the fact that the effects of these two items on economy is not so important; hence respondents don’t consider high amount of significance for these dimensions in Iran community. More over, in behavioral economics of Iran community the amount of reciprocal friendship, inequity aversion and fairness is low that can be attributed to the lack of trust between people in regard to their economic decisions. Practical implications- One of the most important applications of this research, is offering behavioral economy in general scheme, and as regards to few research in this field, it’s one of the main prob-lems of executives when refer to this field of science, because they don’t have appropriate image of the current situation in Iran and by this image they will be able planning decisions regarding the strengths and weaknesses of Iranian society. Originality/value- Firstly, similar research in the field of behavioral economics has not been carried out in Iran, and this study can be considered grounds for starting research in this field. Furthermore, dispite the long time has passed, since the introduction of behavioral economics theory , no research has been focused on this issue in Iran and presented profile in this research , is the first image of be-havioral economics in Iran. Research paper Reference to this paper should be made as follows: Ahmadi, S.A.A., Salamzadeh, Y., and Ranjbar, L. (2013). “Identification and ranking of factors affecting behavioral economics in Iran”, Journal of Entrepreneurship, Business and Economics, Vol. 1 No. 1/2, pp. 101–124.